The state of the late Quaternary megafauna extinction debate: a systematic review and analysis - Stewart, Mathew; Peters, Carli; Ziegler, Michael J.; Carleton, W. Christopher; Roberts, Patrick; Boivin, Nicole; Groucutt, Huw S. (Frontiers in Mammal Science, 2025)
With its origins in the late 18th and early 19th century, the question of what drove the late Quaternary megafauna extinctions remains one of science’s most enduring and hotly contested debates. Once strictly the domain of archaeologists and paleontologists, the topic has attracted growing interest from other disciplines in recent decades, particularly ecologists and conservation biologists, who view these extinctions as a lens through which to inform contemporary conservation and ecosystem management strategies. Alongside this expansion, the field has seen increasing use of advanced analytical and statistical methods. Yet despite these developments, scientific opinion remains deeply divided over the cause(s) of these extinctions. Each year dozens of papers on the topic are published and along with these review articles that cover the debate or certain aspects of it. However, these reviews tend to reflect the viewpoints of their authors. Recognizing this limitation, the present study aimed to offer a more objective, data-driven overview of the field by conducting a systematic review and analysis of the literature. Specifically, we sought to: (1) trace the development of the megafauna extinction debate to understand how it has evolved over time; (2) identify key thematic and conceptual foci within the literature; and (3) use this synthesis of historical trends and interdisciplinary variation to propose a forward-looking research agenda that encourages greater engagement, discussion, integration, and collaboration across fields. Our analysis reveals strong disciplinary divides, uneven temporal and spatial research coverage, and persistent uncertainty over extinction causes. Despite recent major methodological advances, the field remains fragmented, underscoring the need for a research agenda that fosters interdisciplinary collaboration, expands field and legacy studies, as well as species-specific approaches, and integrates cutting-edge scientific and statistical techniques.